Experimental research on the photobiological hydrogen production kinetics of Chlamydomonas reinhardtii GY-D55. (21st September 2016) - He, Zhen-Zong; Qi, Hong; He, Ming-Jian; Ruan, Li-Ming
Abstract: The objective of this paper is to study the photobiological H2 production kinetics of Chlamydomonas reinhardtii ( C. reinhardtii ) GY-D55 experimentally. Special attention is paid to the cultivation of C. reinhardtii GY-D55 and the retrieval of characteristic parameters of the photobiological H2 production kinetic model. A flat-plate airlift photobioreactor is used to cultivate the microalgae. Three different wavelength LED lamps (blue, green and red light) are used as the light source and a standard blackbody (LAND R1500T) is used to calibrate the radiative power of LED lamps. According to the Michaelis–Menten kinetic model, the photobiological kinetic characteristic parameters of C. reinhardtii GY-D55 under different spectra are retrieved, which can be used to support the large-scale production of C. reinhardtii GY-D55. The experimental results showed that a blue or red LED lamp is more benefit for C. reinhardtii GY-D55 to promote photobiological growth rate and photobiological H2 production rate.